Global expansion of chikungunya virus: mapping the 64-year history. (May 2017) - Wahid, Braira; Ali, Amjad; Rafique, Shazia; Idrees, Muhammad
Highlights: Chikungunya virus (CHIKV) is a mosquito-transmitted alphavirus. The global distribution shows that CHIKV is expanding at an alarming rate. CHIKV has the potential to spread to new areas because it is a travel-associated febrile illness. The four different genotypes of CHIKV are Asian, West African, East/Central/South African (ECSA), and Indian Ocean Lineage (IOL). The disease originated in Africa and has since affected the entire globe. This global health menace has affected millions of people in tropical and sub-tropical countries. Summary: Chikungunya virus (CHIKV) is a mosquito-transmitted alphavirus that is emerging as a global threat because of the highly debilitating nature of the associated disease and unprecedented magnitude of its spread. Chikungunya originated in Africa and has since spread across the entire globe causing large numbers of epidemics that have infected millions of people in Asia, the Indian subcontinent, Europe, the Americas, and Pacific Islands. Phylogenetic analysis has identified four different genotypes of CHIKV: Asian, West African, East/Central/South African (ECSA), and Indian Ocean Lineage (IOL). In the absence of well-designed epidemiological studies, the aim of this review article was to summarize the global epidemiology of CHIKV and to provide baseline data for future research on the treatment, prevention, and control of this life-threatening disease.